Implementasi Literasi Digital Melalui Program Sapulidi pada Masa Covid-19: Studi Kasus di Sekolah Menengah Atas - Nur Alim; Fadlansyah Fadlansyah; Hadi Machmud; Sitti Nurfaidah (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2022)
This descriptive qualitative study aims to investigate the implementation of digital literacy during Covid-19 through Sapulidi program at one of high schools in Southeast Sulawesi. Data were garnered through observation, interviews, and documentation from the principal, the head of school literacy team, and members of the Sapulidi team. The findings show that the implementation of digital literacy at the school was carried out in three stages: a) increasing the capacity of facilitators through training for school residents, b) increasing the number and variety of learning resources through the provision of QR code-based digital books on library websites and the use of learning applications, and c) providing computer and internet access in schools and providing digital information through school websites, libraries, and QR codes in the school environment. The forms of QR codes used in the Sapulidi program include the use of in learning, on school plants, on trophy displays, in students' works at school, school literacy galleries, in literacy corners in classroom, and in digital books.KEYWORDS: Covid-19; digital literacy program; high school; QR code